Endoscopic endonasal transsphenoidal approach for pituitary adenomas: technical aspects and report of casuistic Abordagem endoscópica endonasal para adenomas de hipófise: aspectos técnicos e relato de casuística - Américo Rubens Leite dos Santos; Roberto Monteiro Fonseca Neto; José Carlos Esteves Veiga; José Viana Jr; Nilza Maria Scaliassi; Carmen Lúcia Penteado Lancellotti; Paulo Roberto Lazarini (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Analyse technical aspects, effectiveness and morbidity of the endoscopic endonasal transphenoidal approach for pituitary adenomas. METHOD: From January 2005 to September 2008, 30 consecutive patients underwent endoscopic endonasal resection of pituitary adenomas with a follow up from 3 to 36 months. Their medical charts were retrospectively analysed. RESULTS: There were 18 women and 12 men, mean age 44 years (range 17-65 yr). Among the 30 patients, 23 had macroadenomas and 7 microadenomas. Twelve patients had non-functioning tumors, 9 had ACTH-secreting tumors, 8 had GH-secreting tumors and 1 prolactinoma. Complete resection and hormonal control was achieved in all microadenomas. Macroadenomas were completely removed in 6 patients, subtotal resection in 6 and partial resection in 11. Three patients had diabetes insipidus and 5 had CSF leaks treated with lumbar drainage. CONCLUSION: The endonasal endoscopic approach for pituitary tumors is effective and has low morbidity. OBJETIVO: Analisar aspectos técnicos, eficácia e morbidade do acesso transesfenoidal endonasal endoscópico para adenomas hipofisários. MÉTODO: Estudo retrospectivo de trinta pacientes consecutivos submetidos à ressecção endoscópica endonasal de adenomas hipofisários, entre janeiro de 2005 e setembro de 2008, com seguimento pós-operatório entre três e 36 meses. RESULTADOS: Foram operados 18 mulheres e 12 homens com idades variando entre 17 e 65 anos (média 44 anos). Entre os 30 casos operados, 23 eram macroadenomas e sete microadenomas. Doze pacientes apresentavam adenomas não-funcionantes, nove tumores secretores de ACTH, oito tumores secretores de GH e um prolactinoma. Ressecção macroscópica completa e controle endócrino foram conseguidos em todos microadenomas. Ressecção dos macroadenomas foi completa em seis pacientes, subtotal em seis e parcial em seis casos. Três pacientes desenvolveram diabetes insipidus e cinco tiveram fístula liqüórica pós-operatória controlada com drenagem lombar. CONCLUSÃO: A abordagem endoscópica endonasal para adenomas de hipófise é eficaz e apresenta baixa morbidade.